THE ROLE OF MORPHOLOGICAL ANALYSIS IN THE TREATMENT OF ULCER AND ITS COMPLICATIONS - M.Sh. Khakimov; Sh.E. Ashurov; J.K. Dekhkonov; J.Kh. Kushiev (Central Asian Journal of Medicine, 2023)
Bleeding and pyloric stenosis from acute gastric ulcers is a common medical emergency throughout the world. Endoscopic diagnosis and hemostasis are cornerstones in disease management and mortality reduction. The number of urgent open surgical interventions for bleeding acute ulcers continues to decline; in the UK, the surgical intervention rate dropped from 8% to 2% between 1993 and 2006. During the same period in the United States, the use of endoscopic treatment for acute ulcers increased by 58.9%, and the incidence of ulcer disease in emergency surgery decreased by 21.9%.